2006
DOI: 10.1007/s00417-006-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of interferon-alfa therapy in patients with Behçet uveitis

Abstract: A partial or complete response was obtained with IFNalpha therapy in 91% of Turkish patients with Behçet uveitis refractory to conventional immunosuppressive treatment. Our results suggest that there may be differences in therapeutic efficacy and side-effect profile of IFNalpha in different patient populations. Comparative studies are needed to investigate this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 6 publications
0
60
0
6
Order By: Relevance
“…Open-label studies [Boyvat et al 2000;O'Duffy et al 1998;Georgiou et al 1998;Azizlerli et al 1996;Alpsoy et al 1994] Eye involvement Uncontrolled prospective study [Kotter et al 2003] Retrospective studies [Onal et al 2011;Sobaci et al 2010;Deuter et al 2010;Bodaghi et al 2007;Tugal-Tutkun et al 2006;Deuter et al 2004;Krause et al 2003;Calguneri et al 2003;Hamuryudan et al 2002;Wechsler et al 2000;Yalcindag and Uzun, 2012] Systematic review [Kotter et al 2004a] Mucocutaneous disease and arthritis Uncontrolled prospective study [Kotter et al 2004b] Systematic review [Kotter et al 2004a] Neuro-Behçet Case reports [Nichols et al 2001;Kuemmerle-Deschner et al 2008;…”
Section: ]mentioning
confidence: 99%
“…Open-label studies [Boyvat et al 2000;O'Duffy et al 1998;Georgiou et al 1998;Azizlerli et al 1996;Alpsoy et al 1994] Eye involvement Uncontrolled prospective study [Kotter et al 2003] Retrospective studies [Onal et al 2011;Sobaci et al 2010;Deuter et al 2010;Bodaghi et al 2007;Tugal-Tutkun et al 2006;Deuter et al 2004;Krause et al 2003;Calguneri et al 2003;Hamuryudan et al 2002;Wechsler et al 2000;Yalcindag and Uzun, 2012] Systematic review [Kotter et al 2004a] Mucocutaneous disease and arthritis Uncontrolled prospective study [Kotter et al 2004b] Systematic review [Kotter et al 2004a] Neuro-Behçet Case reports [Nichols et al 2001;Kuemmerle-Deschner et al 2008;…”
Section: ]mentioning
confidence: 99%
“…Additionally, in other studies including cases of refractory uveitis, IFN-had similar positive results. These reports were confirmed by Tugal-Tutkun et al, although they reported lower rates of complete response (Tugal-Tutkun et al, 2006). EULAR committee justifies the use of IFN-with or without corticosteroids for eye disease, instead of cyclosporine or azathioprine.…”
Section: Biologic Agents 481 Interferonmentioning
confidence: 72%
“…Hastalar›n %91'inde tam veya k›smi remisyon sa¤lan›rken, sadece %9'unda yan›t al›namam›flt›r. 3 Yak›n zamanda, Sobac› ve ark. 4 taraf›ndan yay›nlanan yeni bir çal›flmada IFN-α tedavisi ile ortalama atak say›s›n›n y›ll›k 3,6'dan 0,56'ya azald›¤› ve olgular›n %28'inde tam remisyon sa¤land›¤› belirtilmifltir.…”
Section: Interferon-alfaunclassified
“…Tedaviye yan›t oranlar› çeflitli yay›nlarda %82-92 aras›nda bildirilmektedir. [3][4][5][6] Öte yandan bu ajan›n Behçet hastal›¤› d›fl›nda nonenfeksiyöz idiopatik üveit, birdshot korioretinopati gibi farkl› endikasyonlarda da baflar›l› oldu¤unu bildiren yay›nlar da mevcuttur. 7 IFN-α kullan›m›na ba¤l› olarak, nezle-benzeri k›rg›n-l›k hali, karaci¤er enzimlerinde yükselme, lökopeni, trombositopeni, depresyon, psoriaziste kötüleflme ve enjeksiyon sahas› ülserleri yan etki olarak tan›mlanmak-la birlikte, ciddi depresyon d›fl›nda genel olarak ilaç b›-rakt›rmay› gerektirecek ciddiyette sorunlar olarak görül-memektedirler.…”
Section: Interferon-alfaunclassified
See 1 more Smart Citation